Drama einer Heldin - Krupkova, Lenka (Musicologica Olomucensia, 2005)
In his opera The Makropulos Case, Leos Janacek simplified Capek's philosophical drama and significantly cut long dialogues. In the third act, he omitted a whole block of text and changed Capek's formal structure. Janacek's addition is Emilie Marty's death. He changed the motivic structure of the dramatic text so that the action would lead teleologically to the end. For these reasons he had to omit everything superfluous, everything that would slow the dramatic tempo. Death as redemption is a traditional operatic conceit, as are the choral scenes at the end. In opposition to Capek's literary model, Janacek in his dramaturgical conception strengthened the structure of the dramatic character of the heroine. His living connection with her is transformed into is own strong attitudes. His concentration on the detailed construction of the character of the heroine as the center of action highlighted the contours of the traits of the secondary characters. Janacek emphasized the compositional assumption of the dramaturgical accents. By restructuring and clarifying individual lines of dramatic action, he emphasized the pulsating rhythms of dramatic situations, so that the libretto carries elements of montage. Janacek changed the text in many places so that the music could become an independent actor in the drama.